2019
DOI: 10.1038/s41598-018-38304-w
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and anti-inflammatory markers in plasma: from late pregnancy to early postpartum

Abstract: During pregnancy, the woman’s body undergoes tremendous changes in immune system adaptation. The immunological shifts that occur in pregnancy can partially be explained by alterations in hormonal levels. Furthermore, during pregnancy, many autoimmune diseases go into remission, only to flare again in the early postpartum period. Given these important changes in the clinical course of a number of autoimmune disorders, surprisingly little has been done to investigate the inflammatory profile changes across pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
96
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 77 publications
15
96
0
4
Order By: Relevance
“…The TNF superfamily of proteins is expressed predominantly by immune cells regulating diverse cell functions, including immune response and inflammation, but also proliferation, differentiation, apoptosis and embryogenesis. A recent Swedish study investigated the inflammatory proteome with the same technology in 22 pregnant women followed longitudinally at two time-points from late pregnancy to week 8 postpartum and found lower levels of TWEAK, TRANCE and TRAIL and higher levels TNFSF14 and OPG during pregnancy in accordance with our findings 20 . In contrast, in their study TNF-beta was higher in pregnancy and TNFRSF9 unchanged but CD40 appeared similar to their results if only comparing our time-points from admission to postpartum.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The TNF superfamily of proteins is expressed predominantly by immune cells regulating diverse cell functions, including immune response and inflammation, but also proliferation, differentiation, apoptosis and embryogenesis. A recent Swedish study investigated the inflammatory proteome with the same technology in 22 pregnant women followed longitudinally at two time-points from late pregnancy to week 8 postpartum and found lower levels of TWEAK, TRANCE and TRAIL and higher levels TNFSF14 and OPG during pregnancy in accordance with our findings 20 . In contrast, in their study TNF-beta was higher in pregnancy and TNFRSF9 unchanged but CD40 appeared similar to their results if only comparing our time-points from admission to postpartum.…”
Section: Discussionsupporting
confidence: 91%
“…A few studies have investigated longitudinal changes in proteins during pregnancy in healthy women [15][16][17][18][19][20] . However, most studies suffer from small sample sizes 15,16,[19][20][21][22][23][24][25] in selected study populations 15,17,24,25 . Some studies have included measurements postpartum 20,21,[23][24][25] in addition to those during pregnancy but no study has included an assessment before conception.…”
mentioning
confidence: 99%
“…Moreover, profound changes in inflammatory and antiinflammatory molecules characterize the pregnancy to PP transition, as recently reported by Brann et al (10) who found a decrease of the major anti-inflammatory markers in the PP period.…”
Section: Immunology Of the Pp Periodsupporting
confidence: 55%
“…Finally, human plasma was found to be an excellent reservoir for cytokines involved in key cancer hallmarks including: pro-inflammatory cytokines (IL-β1, MIP-1a, TNFα, and RANTES) [68,69], chemokines influencing the invasiveness and migration (SDF-1) [70], cytokines supporting tissue repair/ECM degradation and remodeling (TIMP1, TIMP2, MMP1, and MMP9) [71,72], and cytokines promoting cell growth (INF-γ, PDGF-AB, IL-2, and LIF) [69,73]. In addition, cytokines involved in fibrogenesis (EGF, IGF-I, HGF, and PDGF-AB) [74,75] were found in plasma from healthy subjects and BCa patients. CA125 is a common blood marker tested in breast cancer and ovarian cancer and it allows for the identification and distinction of the plasma from BCa patients [76,77].…”
Section: Discussionmentioning
confidence: 99%